The Influence of Job Opportunities, Religiosity and Understanding of Syariah Accounting on Students' Interest in A Career in Syariah Financial Institutions - Mutammimah, Mamik; Juliana Makrufa, Putri (Muhasabatuna : Jurnal Akuntansi Syariah, 2025)
Career opportunities are the availability of jobs. Career opportunities in Islamic financial institutions can provide opportunities for candidates to develop their skills and abilities. This religiosity includes their understanding of the sharia principles applied in Islamic financial institutions as well as their choice of future employment locations. Students gain knowledge of sharia accounting before they start their careers in Islamic financial institutions. This shows that students' interest in getting jobs in Islamic financial institutions continues to increase. So, if students want to work in Islamic financial institutions and want to have a career there, they must understand sharia accounting and religiosity. The purpose of this study was to determine the effect of job opportunities, religiosity and understanding of sharia accounting in sharia financial institutions. The method used in this study is a quantitative approach. The data collection method used is by collecting the population using sampling techniques due to limited time, energy, and costs. The analysis method used is quantitative analysis, namely an analysis tool that uses calculations to determine the extent of the influence between variables and other variables. The results of this study indicate that there is a positive and significant influence of the job opportunity variable (X1) on the interest (Y) of FEBI students in working in sharia financial institutions. There is a positive and significant influence of the religiosity variable (X2) on the interest (Y) of FEBI students in working in sharia financial institutions. There is a positive and significant influence of the understanding of sharia accounting variable (X3) on the interest (Y) of FEBI students in pursuing a career in sharia financial institutions.